Digitalisasi Sistem Pendidikan Dengan Menerapkan Pembelajaran Hibrida Melalui Rekonstruksi Hukum Menggunakan Metode Cognate Bills - Candya Upavata Kutey Karta Negara; Daeli Subrianty; Kamelia Desi Awaliah (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
The education quality in Indonesia occupied 72nd in every 79 countries according to the programme for international student assessment (PISA) survey in 2018. With literacy, mathematics, and science, Indonesia is still below average. For 18 years of assessment, the scores of students' abilities in Indonesia always under the world standard score. Remote learning carried out by the Covid-19 pandemic provided a paradigm shift for Indonesian education toward digitization. This is rising a new learning concept called hybrid learning. In order to achieve a sustainable hybrid learning to improve the quality of education in Indonesia, there are several legal questions about disharmonizing regulations in Indonesia's education sector. This study purposed to know the application of the hybrid learning as a digital transformation of sustainable education in Indonesia also reconstruction of the laws in Indonesian education through the cognate bills methods in order to promote hybrid learning in Indonesia. This study using the normative legal study that uses secondary and tertiary data sources as support data. Data analysis using statute approach, conceptual approach, and analytical approach. Studies indicate that: (1) hybrid learning integrating an interface learning system with online learning as a support tool implemented in Indonesian education systems; (2) the reconstruction of legislation o n the education system in Indonesia through the cognate bills method of accommodating the concept of hybrid learning can be a progressive solution in education transformation. Therefore, with emphasis and centralized effort on the education sector, it is expected to improve the quality of education in Indonesia.